Clinical and Virological Descriptive Study in the 2011 Outbreak of Dengue in the Amazonas, Brazil - Martins, Valquiria do Carmo Alves (Public Library of Science, 2014)
BACKGROUND: Dengue is a vector-borne disease in the tropical and subtropical region of the world and is transmitted by the mosquito Aedes aegypti. In the state of Amazonas, Brazil during the 2011 outbreak of dengue all the four Dengue virus (DENV) serotypes circulating simultaneously were observed. The aim of the study was to describe the clinical epidemiology of dengue in Manaus, the capital city of the state of the Amazonas, where all the four DENV serotypes were co-circulating simultaneously. METHODOLOGY: Patients with acute febrile illness during the 2011 outbreak of dengue, enrolled at the Fundação de Medicina Tropical Dr. Heitor Viera Dourado (FMT-HVD), a referral centre for tropical and infectious diseases in Manaus, were invited to participate in a clinical and virological descriptive study. Sera from 677 patients were analyzed by RT-nested-PCRs for flaviviruses (DENV 1–4, Saint Louis encephalitis virus-SLEV, Bussuquara virus-BSQV and Ilheus virus-ILHV), alphavirus (Mayaro virus-MAYV) and orthobunyavirus (Oropouche virus-OROV). PRINCIPAL FINDINGS: Only dengue viruses were detected in 260 patients (38.4%). Thirteen patients were co-infected with more than one DENV serotype and six (46.1%) of them had a more severe clinical presentation of the disease. Nucleotide sequencing showed that DENV-1 belonged to genotype V, DENV-2 to the Asian/American genotype, DENV-3 to genotype III and DENV-4 to genotype II. CONCLUSIONS: Co-infection with more than one DENV serotype was observed. This finding should be warning signs to health authorities in situations of the large dispersal of serotypes that are occurring in the world.